1971
DOI: 10.1136/bmj.4.5778.22
|View full text |Cite
|
Sign up to set email alerts
|

Thiopropazate Hydrochloride in Persistent Dyskinesia

Abstract: One patient developed severe haematemesis needing inpatient therapy and had to be withdrawn from the trial. In retrospect it was clear that he should not have been admitted to the trial because he had a history of peptic ulceration. DiscussionControlled trials of treatment in Bell's palsy are difficult to perform because of delay in starting therapy which is likely to prejudice the result. For this reason the patients were subdivided into early and late groups. Sixty-six started treatment on the first or secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1972
1972
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In view of its unsatisfactory antipsychotic activity at this dosage and the considerable risk of Parkinsonism with higher doses (Singer and Cheng, 1971), we suggest that its main value is as an adjunctive agent in patients who need to continue other antipsychotic medication. Gerlach et al (1977) reported that the anticholinergic antiparkinsonism drug biperidin aggravated the dyskinesia in all seven patients studied, the changes in the mean dyskinesia score being statistically significant.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In view of its unsatisfactory antipsychotic activity at this dosage and the considerable risk of Parkinsonism with higher doses (Singer and Cheng, 1971), we suggest that its main value is as an adjunctive agent in patients who need to continue other antipsychotic medication. Gerlach et al (1977) reported that the anticholinergic antiparkinsonism drug biperidin aggravated the dyskinesia in all seven patients studied, the changes in the mean dyskinesia score being statistically significant.…”
Section: Discussionmentioning
confidence: 98%
“…The effectiveness of three weeks of treatment with the drug has been demonstrated in two doubleblind cross-over placebo controlled studies, 23 patients in one study (Singer and Cheng, 1971) and two in the other (Roxburgh, 1970).…”
mentioning
confidence: 99%
“…This rationale has led to its successful management by the addition of more of the drug which seems to have caused it, or by adding other antipsychotic drugs, such as thiopropazate, tetrabenazine or reserpine (Singer and Cheng, 1971) . The puzzling cases of acute dystonic reactions, resembling spastic torticollis, are now generally recognised as a drug-induced extrapyramidal reaction and are managed by acute doses of antiparkinsonian drugs.…”
Section: Neurological Side-effectsmentioning
confidence: 99%